EXPERT REVIEW OF THE WeCWI-ENABLED TENCENT APPLICATIONS: INSIGHTS ON ENHANCING IELTS WRITING TASK 2 PERFORMANCE - Chang Bao Suo; Boon Yih Mah; Nur Ilianis Adnan; Hui Zanne Seng (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
In the era of globalisation, English proficiency, especially in IELTS, is crucial for the academic and professional growth of non-native speakers. However, Chinese EFL learners often struggle with IELTS Writing Task 2, where their scores tend to be lower than those in other components. Traditional EFL teaching, especially in IELTS writing, lacks solid theoretical and pedagogical support, and the integration of technological products, such as Tencent apps and WeChat, in IELTS writing teaching and learning, remains unexplored. This study aims to comprehensively assess WETA (WeCWI-enabled Tencent Applications) as a solution to enhance the IELTS Writing Task 2 performance of Chinese English as a Foreign Language (EFL) undergraduates. Four experienced EFL instructors from Chinese tertiary institutions evaluated WETA using a mixed-item checklist, with the data analysed thematically and validity and reliability verified. The results show high praise for WETA in multiple aspects. Its implications lie in potentially revolutionising IELTS Writing Task 2 instruction and learning in China, guiding future technology integration in language teaching and learning. Notably, it fills the research gap in evaluating such pedagogical innovation from instructors’ perspectives and can enhance global language learning outcomes.